Xenophobia and the fallacy of the rainbow nation in selected post- apartheid South African novels - Abdullah, Alshajlawi Mustafa Mohammed (2021)
Xenophobia is increasingly recognized as a serious and worldwide social phenomenon. It is considered as one of the challenging concerns that threaten the social fabric in South Africa. This study focuses on xenophobic representations which are highlighted in selected contemporary South African novels. Previous studies on xenophobia in South African fiction have focussed mostly on the economic and social factors of the phenomenon, however they neglected citizenship attitudes, postcolonial and apartheid legacies. The selected literary texts reflect xenophobia as one of the social concerns that refute the notion of Rainbow Nation that Mandela promised his people to achieve in post-apartheid South Africa. The study argues that the pervasiveness of xenophobic violence in post-apartheid is a result of citizenship attitudes, xenophobic state politics, and the incomplete decolonization from apartheid legacy. I seek to examine the xenophobic violence against black foreigners as reflected in works of fiction through the portrayals of African protagonists living in South Africa. The novels in consideration are: Welcome to Our Hillbrow (2001) by Phaswane Mpe, No Time Like the Present (2012) by Nadine Gordimer, Zebra Crossing (2013) by Meg Vandermerwe, and Evening Primrose (2017) by Kopano Matlwa. The three Postcolonial concepts of Michael Neocosmos’ citizenship and Frantz Fanon’s decolonization and subjectivity are applied as a conceptual framework to investigate the motives behind xenophobic violence against black foreign characters in the aforementioned texts as the selected data for this study. The study also explores how the concepts of citizenship, decolonization, and subjectivity are reflected in the novels through the black African characters’ experiences in South Africa. The study is based on a textual analysis of the protagonists’ experiences, behaviors, thoughts, and speeches by focusing on how African foreigners undergo oppression, racial prejudice, and xenophobic violence as reflected in the novels. The findings reveal that the appearance of xenophobia in post-apartheid is a result of state politics of citizenship and the incomplete decolonization from apartheid legacy. More significantly, the study falsifies the notion of the Rainbow Nation as the findings conclude that South African characters utilize xenophobic violence as a resistance strategy to form their identities and subjectivities.